Biomarkers of Cytokine Release Syndrome Predict Disease Severity and Mortality From COVID-19 in Kidney Transplant Recipients. Issue 1 (January 2021) - Benotmane, Ilies; Perrin, Peggy; Vargas, Gabriela Gautier; Bassand, Xavier; Keller, Nicolas; Lavaux, Thomas; Ohana, Mickael; Bedo, Dimitri; Baldacini, Clément; Sagnard, Mylene; Bozman, Dogan-Firat; Chiesa, Margaux Della; et al.
Abstract : Background: Data on coronavirus disease 2019 (COVID-19) in immunocompromised kidney transplant recipients (KTR) remain scanty. Although markers of inflammation, cardiac injury, and coagulopathy have been previously associated with mortality in the general population of patients with COVID-19, their prognostic impact amongst KTR with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has not been specifically investigated. Methods: We conducted a cohort study of 49 KTR who presented with COVID-19. Clinical and laboratory risk factors for severe disease and mortality were prospectively collected and analyzed with respect to outcomes. The study participants were divided into 3 groups: (1) mild disease manageable in an outpatient setting (n = 8), (2) nonsevere disease requiring hospitalization (n = 21), and (3) severe disease (n = 20). Results: Gastrointestinal manifestations were common at diagnosis. The 30-day mortality rate in hospitalized patients was 19.5%. Early elevations of C-reactive protein (>100 mg/L) and interleukin-6 (>65 ng/L) followed by increases in high-sensitivity troponin I (>30 ng/L) and D-dimer (>960 ng/mL) were significantly associated with severe disease and mortality. Viral load did not have prognostic significance in our sample, suggesting that outcomes were chiefly driven by a cytokine release syndrome (CRS). Conclusions: Regular monitoring of CRS biomarkers in KTR with COVID-19 is paramount to improve clinical outcomes. Abstract : Supplemental Digital Content is available in the text.